1979
DOI: 10.1002/eji.1830090611
|View full text |Cite
|
Sign up to set email alerts
|

The enumeration of rat IgE‐secreting cells using a reverse plaque‐forming cell assay

Abstract: A reverse hemolytic plaque assay utilizing protein A-coated sheep red cells and a specific rabbit anti-rat IgE preparation has been adapted for the enumeration of rat IgE-secreting cells derived from the IR-162 rat plasmacytoma and from rats infected with Nippostrongylus brasiliensis. Under optimal conditions, approximately 10-15% of the viable plasmacytoma cells were scored as plaque-forming cells. In rats infected with 5000 Nippostrongylus brasiliensis larvae, a maximum of 2 x 10(6) IgE-secreting cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…In other stud ies, the BLN have been shown to be sites of IgE syn thesis following local immunization [15]. The near si multaneous appearance of reagin in other tissues, at a time when serum antibody is present makes it difficult to determine other sites of synthesis, although other results [18,26,31] implicate the MLN and, to a lesser extent, the spleen in IgE synthesis in infected rats. Following multiple infections the axillary lymph nodes, which drain the site of larvae injection, also contain IgE-secreting plasma cells [26].…”
Section: Discussionmentioning
confidence: 87%
“…In other stud ies, the BLN have been shown to be sites of IgE syn thesis following local immunization [15]. The near si multaneous appearance of reagin in other tissues, at a time when serum antibody is present makes it difficult to determine other sites of synthesis, although other results [18,26,31] implicate the MLN and, to a lesser extent, the spleen in IgE synthesis in infected rats. Following multiple infections the axillary lymph nodes, which drain the site of larvae injection, also contain IgE-secreting plasma cells [26].…”
Section: Discussionmentioning
confidence: 87%
“…However, RHPA is highly sensitive (Perelmutter et al 1985a, b) and reproducible (Pryjima et al 1980;Konowalchuk et al 1982) in measuring IgE and Ig(G + M) antibodies without employing radioactive substances. In addition, Rector et al (1979) have previously reported that the numbers of nonspecific IgE PFC obtained with RHPA are significantly correlated with circulating nonspecific IgE determined with the radioimmunosorbent test system. Therefore, we used RHPA to measure D.F.…”
Section: Discussionmentioning
confidence: 96%
“…It has been supposed that immunologic regulations may vary in certain lymphoid tissue compartments [28]. IgE-forming cells are mainly detected in respira tory and gastrointestinal mucosa as well as in regional lymph nodes but only a few in the spleen [29,30], and the spleen contains more suppressor cells than the re gional lymph nodes [31]. Homing mostly to the spleen, antigen pulsed SPCs injected intravenously, may effectively produce suppressor cells [22], In fact, suppressor cells are substantially induced by the in jection of antigen pulsed SPCs in our experiments.…”
Section: Discussionmentioning
confidence: 99%